Analisis Soal-Soal Pada Buku Ajar Matematika SMA Kelas X Materi Trigonometri Ditinjau Dari Tipe HOTS - Gina Mahitza; Angriani, Andi Dian; Mardhiah; Nursalam; Lisnasari Andi Mattoliang (Alauddin Journal of Mathematics Education, 2024)
This study aims to describe the characteristics and distribution of Higher Order Thinking Skills type questions in class X high school mathematics textbooks on Trigonometry material of the independent curriculum published by Erlangga in terms of indicators of Higher Order Thinking Skills questions based on the revised Bloom Taxonomy. The type of research used is descriptive qualitative to provide an overview of the characteristics and distribution of HOTS questions on trigonometry material contained in class X mathematics textbooks of the independent curriculum, compiled by Drs. B. K. Noormandiri, M.Pd., published by Erlangga. The subject of this research is the question of each comprehension test in chapter 3 in the grade X high school mathematics textbook on trigonometry material. Data collection uses related documents. In this study, an analysis was conducted to describe the characteristics and distribution of questions based on Anderson & Krathwohl's Revised Bloom Taxonomy on Trigonometry material totaling 40 questions. The results showed that the comprehension test questions contained in class X high school mathematics textbooks, especially on Trigonometry material, there were only 4 questions that could be grouped as HOTS questions. These questions are only in the lowest aspect of HOTS, namely at the cognitive level of analyzing (C4). There is no practice question that can be categorized as HOTS questions in the aspect of analyzing (C5) and creating (C6). The questions in the textbook are uneven in supporting students' higher order thinking skills.